Depth map distortion analysis for view rendering and depth coding - Woo-Shik Kim; Ortega, A.; PoLin Lai; Dong Tian; Gomila, C. (2009 16th IEEE International Conference on Image Processing (ICIP), 2009)
Video representations that support view synthesis based on depth maps, such as multiview plus depth (MVD), have been recently proposed, raising interest in efficient tools for depth map coding. In this paper, we derive a new distortion metric that takes into consideration camera parameters and global video characteristics in order to quantify the effect of lossy coding of depth maps on synthesized view quality. In addition, a new skip mode selection method is proposed based on local video characteristics. Experimental results with the proposed mode selection scheme show coding gains of up to 2 dB for the synthesized views, as well as better subjective quality.